Green Transformation of Supply Chain of Indian Construction Sector via Policy Level Interventions - Vijayadas, S J (Digital Repository of Theses - SSBM Geneva, 2024)
This research study explores the green transformation of the Indian construction sector's supply chain through policy-level interventions. The objectives include assessing key processes that can encompass green supply chain principles, identifying challenges in the Indian context (supply chain management), scrutinizing policy elements influencing green construction via circular or sustainable supply chains, and proposing a conceptual framework to guide policymakers towards achieving carbon-neutrality in the construction industry. The study addresses critical aspects of sustainability (theoretical framework), green supply chain mechanisms (GSCM), barriers to circular economy adoption, experts-driven consensus building (Delphi Analysis), integration of theoretical concepts, enforcement of sustainability criteria by authorities, and the alignment of local-level authorities with sustainability policies. It aims to provide insights into developing comprehensive strategies for greening the Indian construction sector, emphasizing stakeholder collaboration and policy framework development to overcome existing barriers and achieve sustainable development goals. The regulatory tactics employed and their successful strategic implementation mechanisms were thoroughly analyzed during the study of modern construction practices and exceptional scenarios, such as pandemic crises, in order to reach a conclusion for Construction Frameworks (CFW). The construction industry is progressively embracing sustainable practices across all stages, emphasizing eco-friendly design, material procurement (low carbon emissions and minimal embodied energy), transportation (sustainable logistics), energy efficiency (strategic energy management, SEM), waste management (circular economy), and post-construction O&M measures. However, the Indian construction sector faces numerous obstacles in implementing Green Supply Chain Management (GSCM) practices, due to regulatory, logistical, technical, economic, and social barriers. Policy-level interventions are observed to be essential to overcome these challenges and facilitating green transformation in the sector. The study identifies 45 critical environmental sustainability criteria for the Indian construction sector's green transformation of supply chain elements, proposing a conceptual framework (CFW) for policy interventions. Stakeholder consultations and expert reviews validate the framework, underscoring its significance in guiding policymakers towards sustainable construction practices. Policy mapping reveals various regulations influencing sustainability in the construction sector, such as the National Building Code, Environmental Impact Assessment Notification, and Smart Cities Mission. A comprehensive strategy for green supply chain management necessitates capacity building, collaboration, and regulatory strengthening. Educational programs and certification initiatives enhance stakeholder expertise, while collaborative partnerships promote knowledge exchange and resource sharing. Effective policy change models incorporate stakeholder engagement, strategic incentives, and monitoring mechanisms to drive sustainability. The study concludes by emphasizing the need for a unified approach to sustainable construction, combining policy reformulation, stakeholder engagement, and strategic interventions to foster a culture of sustainability within the construction supply chain rather than policy development.